Study on Thermal Balance Analysis Technology of Rail Traffic Gearbox - Wei Ding; Shidang Yan; Weiwei Miao; Lixuan Zhou; Zhongming Liu (Jixie chuandong)
The rail traffic gearbox is a key part of the transmission system in the train. It plays a vital role in the operation of the train. Heat balance analysis of rail traffic gearbox has great influence on the operation of the gearbox. Based on subway gear transmission system， the heat balance equations of the transmission based on thermal network method is established， and the calculation models of heat source，thermal resistance and convective transfer coefficient are given，the temperature of each node is solved by the heat balance equations. The research shows that the efficiency of the rail transit gearbox decreases with the increase of the speed， and the temperature of each node increases with the increase of the speed，and the temperature of the gear meshing point is the highest.